How stable is children‟s affective orientation toward different ethnic groups? A longitudinal study of in-group and out-group attitudes among preschoolers - Enesco, Ileana; Guerrero, Silvia; Lago, María Oliva; Rodríguez, Purificación (Anales de Psicología / Annals of Psychology, 2011)
Most previous research on children‟s ethnic awareness and prejudice has been based on cross-sectional studies; hence we have little information on the intra-individual changes that occur in this area of development. Is there a stable developmental sequence of the different components of ethnic awareness? Does ingroup preference precede outgroup rejection, as cross-sectional studies do suggest? And do children maintain the same affective orientation toward different out-groups? We conducted a longitudinal study with 50 Spanish children aged 4 to 5 years (first measure) and 5 to 6 years (second measure). We assessed several aspects of their ethnic awareness and attitudes toward four groups (Spaniards, Latin Americans, Africans and Asians), within a computer-game context. Results showed a significant ingroup positivity but a lack of outgroup negativity, both at time 1 and 2. In fact, children‟s negative attributions to the ingroup and to the out-groups did not differ. On the other hand, the longitudinal analyses revealed that most children did not change the intensity of their affective orientation to each group, an issue that has received little attention in previous studies.